Evaluating the relationship between financial sustainability and socio-economic development of countries - Viktoriia Kremen; Inna Shkolnyk; Andrii Semenog; Olha Kremen (Central European Economic Journal (CEEJ), 2019)
This paper examines the mainstream theories of "financial sustainability" and "financial development". It is suggested understanding "financial development" as the complex dynamic characteristics of the financial sector, which is formed under the influence of financial and economic policy factors and the financial market functioning. The paper provides the methodology of relationship between financial sustainability and socio-economic development of countries evaluation. Based on the matrix method, it is proved that the differences in developed and developing countries occur due to the relationship between financial sustainability and financial development.
Keywords: G20; G28; O16; 330; financial sustainability; socio-economic development; financial development; financial sector; financial market